2013
DOI: 10.1016/j.exger.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and leucine promote chronological longevity and respiration proficiency during calorie restriction in yeast

Abstract: We have previously shown that autophagy is required for chronological longevity in the budding yeast Saccharomyces cerevisiae. Here we examine the requirements for autophagy during extension of chronological life span (CLS) by calorie restriction (CR). We find that autophagy is upregulated by two CR interventions that extend CLS: water wash CR and low glucose CR. Autophagy is required for full extension of CLS during water wash CR under all growth conditions tested. In contrast, autophagy was not uniformly req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 70 publications
(96 reference statements)
3
60
0
Order By: Relevance
“…As in some other studies (9,63,64), we confirmed the activation of autophagy in the early stationary phase (2-day-old cultures). We used GFP-Atg8, which is a marker of both types of macroautophagy, selective and nonselective macroautophagy (14).…”
Section: Fig 11supporting
confidence: 74%
“…As in some other studies (9,63,64), we confirmed the activation of autophagy in the early stationary phase (2-day-old cultures). We used GFP-Atg8, which is a marker of both types of macroautophagy, selective and nonselective macroautophagy (14).…”
Section: Fig 11supporting
confidence: 74%
“…Thus, autophagy deficiency can lead to TOR inactivation and thereby results in numerous pleiotropic effects. In previous studies, a life-span-prolonging effect originating from TOR inactivation via rapamycin is reported in different organisms 95 - 98 . However, only in a few cases, this increase is unequivocally correlated with Atg genes 99 , 100 .…”
Section: Discussionmentioning
confidence: 90%
“…These include chromatin remodeling factors (Dang et al, 2014), maintenance of cellular ATP levels (Choi and Lee, 2013), autophagy and lipid homeostasis (Aris et al, 2013; Lester et al, 2013; Richard et al, 2013), rDNA replication (Kwan et al, 2013), nitric oxide (Li et al, 2011), and glutathione and redox homeostasis (Mannarino et al, 2008; Molin et al, 2011), among others. The relationship of each of these to the established longevity mechanisms and to each other will require additional study.…”
Section: Dietary Restriction In S Cerevisiaementioning
confidence: 99%